Defective autophagosome formation in p53-null colorectal cancer reinforces crocin-induced apoptosis - Amin, Amr; Bajbouj, Khuloud; Koch, Anna Maria; Gandesiri, Muktheshwar; Schneider-Stock, Regine (International Journal of Molecular Sciences, 2015)
Crocin, a bioactive molecule of saffron, inhibited proliferation of both HCT116 wild-type and HCT116 p53(-/-) cell lines at a concentration of 10 mM. Flow cytometric analysis of cell cycle distribution revealed that there was an accumulation of HCT116 wild-type cells in G1 (55.9%, 56.1%) compared to the control (30.4%) after 24 and 48 h of crocin treatment, respectively. However, crocin induced only mild G2 arrest in HCT116 p53(-/-) after 24 h. Crocin induced inefficient autophagy in HCT116 p53(-/-) cells, where crocin induced the formation of LC3-II, which was combined with a decrease in the protein levels of Beclin 1 and Atg7 and no clear p62 degradation. Autophagosome formation was not detected in HCT116 p53(-/-) after crocin treatment predicting a nonfunctional autophagosome formation. There was a significant increase of p62 after treating the cells with Bafilomycin A1 (Baf) and crocin compared to crocin exposure alone. Annexin V staining showed that Baf-pretreatment enhanced the induction of apoptosis in HCT116 wild-type cells. Baf-exposed HCT116 p53(-/-) cells did not, however, show any enhancement of apoptosis induction despite an increase in the DNA damage-sensor accumulation, ?H2AX indicating that crocin induced an autophagy-independent classical programmed cell death.
EVALuna2:6730